2021
DOI: 10.1002/adhm.202002058
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies on the Role of Oxygen Gradient and Culture Condition on Mesenchymal Stem Cell Fate

Abstract: Over the past few years, mesenchymal stem (or stromal) cells (MSCs) have garnered enormous interest due to their therapeutic value especially for their multilineage differentiation potential leading to regenerative medicine applications. MSCs undergo physiological changes upon in vitro expansion resulting in expression of different receptors, thereby inducing high variabilities in therapeutic efficacy. Therefore, understanding the biochemical cues that influence the native local signals on differentiation or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 101 publications
2
53
0
1
Order By: Relevance
“…, 1–6% in the bone marrow). A large body studies have demonstrated that hypoxia culture of MSCs leads to enhanced secretion of various growth factors (GFs), as well as exosome cargo with improved therapeutic potential [ 16 , 17 ]. Recent works proved that the hypoxic condition of 1% O 2 induced the release of sEVs from various MSCs (e.g., bone marrow MSCs [ 18 ], and human umbilical cord MSCs [ 19 ]), hence enhancing the therapeutic efficacy of MSCs exosomes for treating multiple defects.…”
Section: Introductionmentioning
confidence: 99%
“…, 1–6% in the bone marrow). A large body studies have demonstrated that hypoxia culture of MSCs leads to enhanced secretion of various growth factors (GFs), as well as exosome cargo with improved therapeutic potential [ 16 , 17 ]. Recent works proved that the hypoxic condition of 1% O 2 induced the release of sEVs from various MSCs (e.g., bone marrow MSCs [ 18 ], and human umbilical cord MSCs [ 19 ]), hence enhancing the therapeutic efficacy of MSCs exosomes for treating multiple defects.…”
Section: Introductionmentioning
confidence: 99%
“…In an ACY (-) group, MSCs were cultured as previously described ( Henrionnet et al, 2017 ; Samal et al, 2021 ). In brief, the culture medium contained low glucose DMEM (Gibco) supplemented with FBS (10%, Hyclone), fibroblast growth factor-basic (bFGF, 1 ng/ml, PeproTech), and penicillin/streptomycin (1%, Gibco).…”
Section: Methodsmentioning
confidence: 99%
“…The potential application of stem cells for tissue regeneration represents an important challenge but it is necessary to optimize cell culture conditions to preserve the desired stem cell properties. As reported, some in vitro parameters can influence stem cell characteristics and reduce cellular proliferation supporting senescence [170]. One prominent characteristic of stem cells is their natural aptitude to reside in low O 2 condition niches.…”
Section: Exploitation Of Hypoxia For Regenerative Medicine Purposesmentioning
confidence: 96%
“…In literature, there are evidence supporting complex link connecting hypoxia, metabolism, HIFs, and several molecules with crucial roles in the regulation of stemness or differentiation (Figure 6). Low O 2 tension can upregulate proliferation and the expression of pluripotency-related genes, probably by mimicking the conditions that stem cells experience in vivo [170]. In turn, these stemness factors can regulate other subordinate genes involved in the metabolic control of stemness [204] allowing the preservation of a more undifferentiated state and genetic stability (Figure 6).…”
Section: O 2 For Stemness Preservationmentioning
confidence: 99%